2008
DOI: 10.1021/jf8022782
|View full text |Cite
|
Sign up to set email alerts
|

Total Polyphenol Content and Antioxidant Capacity of Commercially Available Tea (Camellia sinensis) in Argentina

Abstract: Tea, Camellia sinensis (L.) O. Kuntze (Theaceae) is cultivated in Argentina in the northeastern region (provinces of Misiones and Corrientes), between 26 degrees and 28 degrees south latitude, the southernmost area of the world where tea is cultivated. The objective of this work was to determine the total polyphenol content and the in vitro antioxidant capacity of green and black tea cultivated and industrialized in Argentina. Twelve samples of eight brands were analyzed. The total polyphenol content was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
186
8
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(219 citation statements)
references
References 33 publications
17
186
8
8
Order By: Relevance
“…Lower PAL activity correlated with lower synthesis of flavones such as epigallocatechin gallate (EGCG) and epicatechin gallate (ECG), (which are important precursors of theaflavin-3, 3â€Č-digallate) that determines final tea quality (Jeyaramraja et al 2003). The antioxidant activities were well correlated with the total polyphenol content in tea was experimentally reinforced by Anesini et al (2008).…”
Section: Resultsmentioning
confidence: 99%
“…Lower PAL activity correlated with lower synthesis of flavones such as epigallocatechin gallate (EGCG) and epicatechin gallate (ECG), (which are important precursors of theaflavin-3, 3â€Č-digallate) that determines final tea quality (Jeyaramraja et al 2003). The antioxidant activities were well correlated with the total polyphenol content in tea was experimentally reinforced by Anesini et al (2008).…”
Section: Resultsmentioning
confidence: 99%
“…Correlation analysis between the levels of total polyphenols and catechins and EC 50 values were undertaken and both were greatly correlated with DPPH assays (r 2 =0.607 and r 2 =0.654, respectively). Previous studies reported similar correlations between these parameters for green tea and other types of tea products (Fukushima et al 2009;Anesini et al 2008;Karori et al 2010). It was inferred that DPPH radicalscavenging activity was likely due to polyphenols and catechins existed in the Qingzhuan tea extracts.…”
Section: Resultsmentioning
confidence: 53%
“…Phenolic content and antioxidant activity are parameters of quality for tea pertaining to its biological properties (Anesini et al, 2008). For this reason, several studies have been performed to evaluate these parameters and their functional properties (e.g., anti-inflammatory or anticarcinogenic activity) (Yao et al, 2006;Chan et al, 2007;Anesini et al, 2008;Nishiyama et al, 2010;Senger et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, several studies have been performed to evaluate these parameters and their functional properties (e.g., anti-inflammatory or anticarcinogenic activity) (Yao et al, 2006;Chan et al, 2007;Anesini et al, 2008;Nishiyama et al, 2010;Senger et al, 2010). In our study, green tea was used as another reference (in addition to the pure substances, quercetin, and gallic acid) due to its abundance of flavonoids, including catechins and their derivatives, which may constitute up to 30% of its dry weight (Lorenzo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%